Electrochemical devices, electrodes for electrochemical devices, coating fluids for electrochemical devices, and uses thereof
By using polymer adhesives with high molecular weight and polymer weight distribution in electrochemical equipment, the problem of adhesives affecting the contact area of active materials in the prior art is solved, and higher charge and discharge rate and performance stability are achieved.
Patent Information
- Application Number
- JP2021567646
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-10-07
- Filing Date
- 2020-12-24
- Publication Date
- 2025-04-30
- Estimated Expiration
- 2040-12-24
AI Technical Summary
In existing non-aqueous electrochemical devices, adhesives adhere to the surface of the active material, resulting in a decrease in the contact area between the electrolyte and the active material, affecting the charge and discharge rate and performance stability of the equipment.
The polymer with a molecular structure containing specific units is used as the binder to ensure that its application in electrochemical equipment has high molecular weight and polymer weight distribution, and enhance the thermal stability and adhesion of the binder.
It improves the charge and discharge rate and performance stability of electrochemical equipment, and enhances the durability and electrochemical stability of the equipment.
Smart Images

Figure 0007669934000012 
Figure 0007669934000001 
Figure 0007669934000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a non-aqueous electrochemical device such as a lithium ion primary battery, a lithium ion secondary battery, etc. The present invention also relates to an electrode for the electrochemical device, a coating liquid for forming a member for the electrochemical device, and uses thereof. [Background technology]
[0002] In general, a non-aqueous electrochemical device such as a primary battery or a secondary battery comprises an exterior body and contents for realizing the functions of the device, such as electrodes and an electrolyte solution enclosed therein. The electrodes include an active material layer and, if necessary, a current collector. The active material layer may be a foil body of a metal active material, or may be a composite layer containing a particulate active material. Since the composite layer contains a particulate active material, it is generally made of a porous material, and is used in the device in a state of being impregnated with an electrolyte solution.
[0003] In most cases, the mixture layer contains a binder in addition to the active material. The particulate active material is held in the mixture layer by the mixture layer containing the binder. Various substances have been proposed as the binder (for example, Patent Documents 1 and 2). [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2003-272634 A [Patent Document 2] JP 2011-40318 A Summary of the Invention [Problem to be solved by the invention]
[0005] The binder is necessary for the active material to be well retained in the composite layer, but it also has the property of impairing the performance of the device. That is, the composite layer is impregnated with an electrolyte, and the electrolyte contacts the particulate active material, so that the device exhibits its performance. However, when the binder is attached to the surface of the active material, the exposed surface area of the active material is reduced, and the electrolyte is prevented from contacting the active material. As a result, the charge / discharge rate is reduced, and the performance of the device, such as the rate characteristics, may be reduced.
[0006] Furthermore, the low durability of the binder itself may impair the performance of the device. For example, when the binder deteriorates due to charging and discharging of the device, the performance of the device, such as the resistance retention rate and the discharge amount retention rate, may decrease.
[0007] Therefore, an object of the present invention is to provide an electrochemical device having a high charge / discharge rate, high durability, and excellent performance such as rate characteristics, resistance retention rate, and discharge amount retention rate, as well as an electrode and a coating liquid for constituting such an electrochemical device, and uses thereof. [Means for solving the problem]
[0008] The present inventors have conducted research to solve the above problems, and as a result, have found that the above problems can be solved by using a polymer having a specific structure and molecular weight as a material constituting a binder, and have completed the present invention. That is, the present invention is as follows.
[0009] [1] A non-aqueous electrochemical device, A polymer (P) is contained within the electrochemical device, The polymer (P) is a polymer having a molecular structure containing a unit (P) represented by the following formula (P) and a mass average molecular weight of more than 50,000: [ka] R in formula (P) P is a group having 1 to 20 carbon atoms. [2] The electrochemical device according to [1], wherein the proportion of the units (P) in the polymer (P) molecules is 50 mass % or more. [3] The polymer (P) has, as the unit (P), the R P The electrochemical device according to [1] or [2], wherein the unit is a methyl group or an ethyl group. [4] The polymer (P) has, as the unit (P), the R P The electrochemical device according to any one of [1] to [3], comprising a unit which is a group having 3 to 20 carbon atoms. [5] The polymer (P) has, as the unit (P), the R P The electrochemical device according to any one of [1] to [4], comprising a unit in which the unit is a group containing a crosslinked structure. [6] The polymer (P) has, as the unit (P), the R P The electrochemical device according to any one of [1] to [5], wherein the unit is a fluorine-containing group. [7] Further comprising an electrolyte; The electrochemical device according to any one of [1] to [6], wherein the amount of the polymer (P) is 5 parts by mass or more per 100 parts by mass of the electrolytic solution. [8] An electrode for a non-aqueous electrochemical device comprising a particulate active material and a polymer (P), The polymer (P) is a polymer having a molecular structure containing a unit (P) represented by the following formula (P) and a mass average molecular weight of more than 50,000: [ka] R in formula (P) P is a group having 1 to 20 carbon atoms. [9] The electrode for electrochemical devices according to [8], wherein the proportion of the units (P) in the polymer (P) molecules is 50 mass % or more.
[10] The polymer (P) comprises, as the unit (P), the R P The electrode for electrochemical devices according to [8] or [9], wherein the unit is a methyl group or an ethyl group.
[11] The polymer (P) has, as the unit (P), the R P The electrode for electrochemical devices according to any one of [8] to
[10] , comprising a unit which is a group having 3 to 20 carbon atoms.
[12] The electrode for electrochemical devices according to any one of [8] to
[11] , wherein the amount of the polymer (P) per 100 parts by mass of the particulate active material is more than 1 part by mass.
[13] The electrode for electrochemical devices according to any one of [8] to
[12] , comprising a mixture layer containing the particulate active material and the polymer (P), and a current collector layer.
[14] The electrode for electrochemical devices according to
[13] , wherein the current collector layer is a metal layer.
[15] The electrode for electrochemical devices according to
[13] or
[14] , wherein the current collector layer has an unevenness of Ry500 nm or more on a surface thereof in contact with the mixture layer.
[16] A coating liquid for electrochemical devices comprising a polymer (P), The polymer (P) is a polymer having a molecular structure containing a unit (P) represented by the following formula (P) and a mass average molecular weight of more than 50,000: [ka] R in formula (P) P is a group having 1 to 20 carbon atoms.
[17] The coating fluid for electrochemical devices according to
[16] , wherein a proportion of the units (P) in the molecules of the polymer (P) is 50 mass % or more.
[18] The polymer (P) comprises, as the unit (P), the R P The coating fluid for electrochemical devices according to
[16] or
[17] , wherein the unit is a methyl group or an ethyl group.
[19] The polymer (P) comprises, as the unit (P), the R P The coating fluid for electrochemical devices according to any one of
[16] to
[18] , comprising a unit which is a group having 3 to 20 carbon atoms.
[20] The polymer (P) comprises, as the unit (P), the R PThe coating fluid for electrochemical devices according to any one of
[16] to
[19] , comprising a unit in which
[21] The coating fluid for electrochemical devices according to any one of
[16] to
[20] , which has a slurry-like property.
[22] An insulating layer for an electrochemical device, comprising a layer obtained by curing the coating liquid according to any one of
[16] to
[21] .
[23] The insulating layer according to
[22] , which contains a crosslinked product of the polymer (P) formed by the curing.
[24] An electrode for an electrochemical device, comprising a layer obtained by curing the coating liquid according to any one of
[16] to
[21] .
[25] The electrode according to
[24] , comprising a crosslinked product of the polymer (P) formed by the curing.
[26] An undercoat layer for an electrochemical device, comprising a layer obtained by curing the coating liquid according to any one of
[16] to
[21] .
[27] The undercoat layer according to
[26] , comprising a crosslinked product of the polymer (P) formed by the curing.
[28] An electrolyte solution for electrochemical devices, comprising a polymer (P), The polymer (P) is a polymer having a molecular structure containing a unit (P) represented by the following formula (P) and a mass average molecular weight of more than 50,000: [ka] R in formula (P) P is a group having 1 to 20 carbon atoms.
[29] The liquid electrolyte for electrochemical devices according to
[28] , wherein the proportion of the units (P) in the molecules of the polymer (P) is 50 mass % or more.
[30] The polymer (P) comprises, as the unit (P), the R P The electrolyte solution for electrochemical devices according to
[28] or
[29] , wherein the unit is a methyl group or an ethyl group.
[31] The polymer (P) comprises, as the unit (P), the R PThe liquid electrolyte for electrochemical device according to any one of
[28] to
[30] , which contains a unit which is a group having 3 to 20 carbon atoms.
[32] The polymer (P) comprises, as the unit (P), the R P The liquid electrolyte for electrochemical device according to any one of
[28] to
[31] , comprising a unit in which Effect of the Invention
[0010] According to the present invention, there are provided an electrochemical device having a high charge / discharge rate, high durability, and excellent performance in terms of rate characteristics, resistance retention rate, discharge amount retention rate, etc., as well as an electrode and a coating liquid for constituting such an electrochemical device, and uses thereof. [Brief description of the drawings]
[0011] [Figure 1] FIG. 1 is a graph showing the experimental results of Reference Example 1 of the present application. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] Hereinafter, the present invention will be described in detail with reference to embodiments and examples. However, the present invention is not limited to the embodiments and examples described below, and may be modified and implemented as desired without departing from the scope of the claims of the present invention and the scope of equivalents thereto.
[0013] In the following description, the term "solvent" is interpreted in a broad sense and includes the meaning of a dispersion medium. That is, the term "solvent" includes not only a medium in a solution (i.e., a mixture of a liquid medium substance and a solute substance dissolved therein), but also a medium in a dispersion (i.e., a mixture of a liquid medium substance and a dispersion substance dispersed therein as solid particles or emulsion particles), and a medium in a mixture containing both a solute and a dispersion substance.
[0014] In the following description, unless otherwise specified, "(meth)acrylate" is a term that includes "acrylate", "methacrylate" and mixtures thereof.
[0015] [1. Overview of electrochemical devices] The electrochemical device of the present invention is a non-aqueous electrochemical device. That is, the electrochemical device of the present invention includes contents such as electrodes and an electrolyte solution sealed in a sealed space inside the device container, and the contents are composed of liquids and solids other than water. The liquid sealed in the device may contain a trace amount of water, but in that case, the concentration is 10,000 ppm or less, preferably 1,000 ppm or less, and more preferably 500 ppm or less. On the other hand, the container is a component for forming a sealed space within the device, and the material is not particularly limited as long as it has physical properties that allow the formation of such an internal space. The material constituting the container does not exist within the space inside the container, and therefore is not included in the category of materials enclosed within the electrochemical device.
[0016] [2. Polymer (P)] The electrochemical device of the present invention contains a polymer (P) encapsulated therein. The polymer (P) is a polymer having a molecular structure containing a unit (P) represented by the following formula (P):
[0017] [ka]
[0018] R in formula (P) P R is a group having 1 to 20 carbon atoms. P R may be a straight chain, a branched chain, or may have a ring structure. P R may be a hydrocarbon group or a group containing elements other than carbon and hydrogen. P R may have an ether structure, an amine structure, or both of them in the middle of the chain. Pmay further contain a hetero element such as a halogen atom, for example a fluorine atom.
[0019] R P may include a crosslinked structure. Here, the crosslinked structure is a structure in which the polymer (P) is bonded to another R P Therefore, R P When R has a bridge structure, multiple R P For example, the polymer (P) contained in the material for producing the electrochemical device of the present invention may contain a crosslinked structure. P In the manufacturing process of an electrochemical device, a polymer (P) containing a crosslinked structure is used, and the crosslinked partial structure is subjected to a crosslinking reaction, whereby an electrochemical device containing a polymer (P) containing a crosslinked structure can be manufactured. P By including a crosslinked structure as the crosslinking group, the durability of the electrochemical device can be further improved. Examples of the crosslinkable partial structure include a carbon-carbon unsaturated bond (double bond or triple bond), an epoxy group, an oxetane group, a carboxyl group, an acetoacetyl group, an isocyanate group, a thiol group, or a combination thereof. By having such a structure, a crosslinking reaction can occur to form a crosslink.
[0020] R P In the case where the polymer (P) is used as a material for the mixture layer and the mixture layer further contains a carbon material such as a carbon active material, R P The aromatic ring is preferably present because it increases the affinity between the polymer (P) and the carbon material. Examples of the aromatic ring include, but are not limited to, a phenyl group, a naphthyl group, an anthracenyl group, a pyrenyl group, and a biphenyl group, and may be a ring having a larger number of carbon atoms than these.
[0021] In one embodiment, R P The number of carbon atoms in R is preferably 1 to 2. PWhen the carbon number is within the range of 1 to 2, it is possible to obtain affinity with an appropriate solvent in many cases, and it is possible to obtain an electrochemical device having a high charge / discharge rate, high durability, and excellent performance such as rate characteristics, resistance retention rate, and discharge amount retention rate. In addition, the polymer (P) can be well dissolved in a coating liquid containing water as a solvent. In another embodiment, R P The number of carbon atoms in R is preferably 3 to 20. P By making the number of carbon atoms to be from 3 to 20, the lipophilicity of the polymer (P) can be increased, which is preferable when a polymer (P) with high lipophilicity is required.
[0022] R P More specific examples of the alkyl group include methyl, ethyl, propyl, butyl, alkyl groups having a larger number of carbon atoms than the butyl group, phenyl, oxyethylene chains, and fluorinated alkyl groups of various lengths. These may have a cyclic structure.
[0023] R P By appropriately selecting the type of R, the degree of properties such as hydrophilicity of the polymer (P) can be adjusted. For example, P By increasing the ratio of one or more of methyl groups, ethyl groups, propyl groups, and oxyethylene chains among all R in the polymer (P), a highly hydrophilic polymer (P) can be obtained, and for example, the polymer (P) can be made a water-soluble substance. P By increasing the proportion of at least one of the butyl group or an alkyl group having a carbon number greater than that of the butyl group, and the phenyl group, a polymer (P) having high lipophilicity can be obtained. P By increasing the proportion of the fluorine-containing groups among them, a polymer (P) having high water repellency can be obtained.
[0024] The polymer (P) may be a homopolymer consisting of only one type of unit (P), a copolymer consisting of multiple types of units (P), or a copolymer consisting of one or multiple types of units (P) and other units. When the polymer (P) is a copolymer, the copolymer may be in the form of a random copolymer, a block copolymer, a graft copolymer, or the like. When the polymer (P) contains units other than the unit (P), examples of such units include (meth)acrylate units obtained by polymerization of (meth)acrylates such as methyl (meth)acrylate and ethyl (meth)acrylate.
[0025] However, when the polymer is a copolymer, the proportion of the units (P) in the polymer (P) molecule is preferably 50% by mass or more, more preferably 60% by mass or more. The upper limit of this proportion can be 100% by mass. In addition, the molecular structure of the polymer (P) preferably includes a structure in which three or more units (P) are continuously bonded. By having such a structure, it is possible to obtain an electrochemical device having a high charge / discharge rate, high durability, and excellent performance such as rate characteristics, resistance retention rate, and discharge amount retention rate.
[0026] The mass average molecular weight of the polymer (P) is more than 50,000, preferably 100,000 or more, more preferably 150,000 or more, and even more preferably 200,000 or more. The upper limit of the mass average molecular weight is not particularly limited, but may be 10,000,000 or less. By having the mass average molecular weight be equal to or greater than the lower limit, the mechanical strength of the device components containing the polymer (P) can be increased, and an electrochemical device having a high charge / discharge rate, high durability, and excellent performance such as rate characteristics, resistance retention rate, and discharge amount retention rate can be obtained. In particular, by having the mass average molecular weight be a large value other than the lower limit, good lubricating performance can be expressed. By having the mass average molecular weight be equal to or less than the upper limit, the handleability of the polymer (P) can be improved.
[0027] The molecular weight distribution of the polymer (P) is preferably 1.0 or more, more preferably 1.1 or more, while it is preferably 10 or less, more preferably 5.0 or less, and even more preferably 3.0 or less. The molecular weight distribution is a value (Mw / Mn) represented by the ratio of the mass average molecular weight (Mw) to the number average molecular weight (Mn). The molecular weight and molecular weight distribution values can be measured by GPC (gel permeation chromatography) using polyethylene oxide as a standard substance.
[0028] Without being bound to a particular theory, the mechanism by which the electrochemical device of the present invention obtains the effects of the present invention by containing the polymer (P) is believed to be as follows. Since the unit (P) constituting the polymer (P) contains an amide structure (-CO-N), the polymer (P) has high heat resistance and can exhibit strong adhesion to other components constituting the device, such as a current collector, a separator substrate, and a particulate active material. This is thought to increase resistance to various stresses in an electrochemical device. When the polymer (P) exists as a solid, it functions as an adhesive. When the polymer (P) is dissolved in a liquid or exists in a swollen state due to impregnation with a liquid, it also exhibits adhesion and lubricity, and can reduce the degree of damage to the device due to friction when the electrochemical device is subjected to an internal or external force. In addition, the polymer (P) has an extremely wide potential window (see Reference Example 1). This is also thought to be due to the inclusion of a chemically stable amide structure. When an electron-withdrawing substituent (e.g., fluorine) is introduced into the polymer (P), the oxidation resistance is further improved, and when an electron-donating substituent (e.g., long-chain alkyl) is introduced, the reduction resistance is further improved. The higher the molecular weight of the polymer (P), the lower the chemical reactivity and diffusion rate, and therefore the lower the reaction volume per unit time, resulting in higher electrochemical stability. Also, the higher the molecular weight of the polymer (P), the lower the proportion of chain ends with relatively high chemical reactivity, which is preferable. It is even more preferable for the polymer (P) to have a ring structure. When the polymer (P) is used in an electrochemical device, it is possible to construct a device in which resistance is unlikely to increase over the long term. It is believed that the fact that it is unlikely to impede the movement of ions suppresses deterioration of the device.
[0029] The method for producing the polymer (P) is not particularly limited, and the polymer can be produced by a known production method. Examples of the method for producing the polymer (P) include ring-opening polymerization of a compound having an oxazoline ring, acylation of polyethyleneimine, polymerization of a macromer having an oxazoline chain, and graft polymerization from a polymer having an initiator group on the side chain. When a macromer having an oxazoline chain is copolymerized with another polymer, a block copolymer containing the unit (P) and another polymerized unit can be produced. Examples of the copolymerizable polymer include silicone, polylactic acid, and polyethylene oxide.
[0030] In the case of producing a polymer (P) having a crosslinked structure, a crosslinking reaction may be carried out. P A polymer (P) having a crosslinkable partial structure as a crosslinking group or a polymer having other crosslinkable groups is used as a material, and a crosslinking reaction suitable for the crosslinkable structure is carried out to obtain a polymer (P) having a crosslinked structure. Examples of the crosslinking reaction include photocrosslinking, thermal crosslinking, electron beam crosslinking, radiation crosslinking, and ion crosslinking.
[0031] An example of the compound having an oxazoline ring is a compound represented by the following formula (P2).
[0032] [ka]
[0033] R in formula (P2) P and preferred examples thereof include R in formula (P) P The terminal group of the polymer (P) is not particularly limited, and may be a terminal group obtained by ring-opening of a normal oxazoline derivative, or may be a terminal group that undergoes addition or polymerization of various functional groups or additional groups depending on the selection of a polymerization initiator or terminator. For example, it may be an alkyl group such as a methyl group, a hydroxyl group, a thiol, a vinyl group, an alkyne, an azide, a piperazine, an acrylate, a methacrylate, an epoxide, or the like.
[0034] In the electrochemical device of the present invention, the polymer (P) can be present mainly in the composite layer (i.e., the positive electrode composite layer and / or the negative electrode composite layer) as a binder that binds particulate active materials. The polymer (P) can also be present in a layer other than the composite layer, for example, in an insulating layer, as a binder that binds particles such as inorganic particles that constitute the insulating layer. The polymer (P) can be present as an undercoat layer, interposed between two layers (for example, between a current collector and a composite layer). According to the present inventor's discovery, the polymer (P) has the above-mentioned specific structure and molecular weight, and can exhibit good performance as a binder while being well impregnated with an electrolytic solution. As a result, an electrochemical device having a component (composite layer, insulating layer, undercoat layer, etc.) containing the polymer (P) can be an electrochemical device having a high charge / discharge rate, high durability, and excellent performance such as rate characteristics, resistance retention rate, and discharge amount retention rate.
[0035] The polymer (P) may also be present as a component of the electrolyte. In the electrochemical device of the present invention, a part of the polymer (P) that was a component at the time of manufacturing the electrode mixture layer may be present in a state of dissolving in the electrolyte. The mass of the polymer (P) in the electrochemical device of the present invention may be defined relative to the total amount of the electrolyte enclosed in the electrochemical device. Specifically, the amount of the polymer (P) relative to 100 parts by mass of the electrolyte may be preferably 5 parts by mass or more, more preferably 10 parts by mass or more, and even more preferably 15 parts by mass or more. The upper limit of the amount of the polymer (P) relative to 100 parts by mass of the electrolyte is not particularly limited, but may be, for example, 50 parts by mass or less. In the device, the polymer (P) is mainly present as a component of the electrode mixture layer, and a part of the polymer (P) is present in a state of dissolving in the electrolyte, and particularly, the amount of the polymer (P) relative to the electrolyte is preferably the lower limit or more. In that case, the dissolution of the polymer (P) from the electrode mixture layer can be suppressed, and the performance of the device can be maintained for a longer period of time.
[0036] In the electrochemical device of the present invention, an example of an electrode having a composite layer containing the polymer (P) is an electrode for electrochemical devices described below.
[0037] The electrochemical device of the present invention may comprise, in addition to the electrodes, components that an electrochemical device typically comprises, such as an electrolyte and an insulating layer.
[0038] As the electrolyte, an organic electrolyte in which a supporting electrolyte is dissolved in an organic solvent is usually used. When the electrochemical device is a lithium ion secondary battery, a lithium primary battery, or an electrochromic device, an example of the supporting electrolyte is a lithium salt. An example of the lithium salt is LiPF 6 , LiAsF 6 , LiBF 4 , LiB(C 2 O 4 )F 2 , LiB(C 2 O 4 ) 2 , LiSbF 6 , LiAlCl 4 , LiClO 4 , C.F. 3 SO 3 Li, C. 4 F 9 SO 3 Li, C.F. 3 COOLi, (CF 3 CO) 2 NLi, (CF 3 SO 2 ) 3 CLi, (FSO 2 ) 2 NLi, (CF 3 SO 2 ) 2 NLi, and (C 2 F 5 SO 2 Among them, LiBF is the most popular because it is easily soluble in solvents and has a high degree of dissociation. 4 , LiPF 6 , (CF 3 SO 2 ) 2 NLi, (FSO 2 ) 2 NLi is preferred, LiPF 6 , (CF 3 SO 2 ) 2 NLi, (FSO2 ) 2 NLi is particularly preferred. As the supporting electrolyte, one type may be used alone, or two or more types may be used in combination at any ratio. In the case where the electrochemical device is a capacitor, the supporting electrolyte may be, for example, the above-mentioned lithium salt, or may be, for example, an onium salt. Examples of the onium salt include, but are not limited to, triethylmethylammonium tetrafluoroborate, tetraethylammonium tetrafluoroborate, N,N-diethyl-N-methyl-N-(2-methoxyethyl)ammonium bis(trifluoromethanesulfonyl)imide, 1-ethyl-3-methylimidazolium tetrafluoroborate, 1-ethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide, and N,N-diethyl-N-methyl-N-(2-methoxyethyl)-tetrafluoroborate, and other nitrogen cations, phosphorus cations, and the like may be used. As the supporting electrolyte, one type may be used alone, or two or more types may be used in combination at any ratio. If the electrochemical device is any other device, a supporting electrolyte may be selected that contains the carrier ions of the device.
[0039] As the organic solvent, which is a component of the electrolytic solution, a solvent capable of dissolving the supporting electrolyte can be appropriately selected. Examples of the organic solvent include carbonates such as dimethyl carbonate (DMC), ethylene carbonate (EC), diethyl carbonate (DEC), propylene carbonate (PC), butylene carbonate (BC), and ethyl methyl carbonate (EMC); esters such as γ-butyrolactone and methyl formate; ethers such as 1,2-dimethoxyethane and tetrahydrofuran; sulfur-containing compounds such as sulfolane and dimethyl sulfoxide; and mixtures thereof. Among them, carbonates are preferred because they have a high dielectric constant and a wide stable potential range. In particular, a mixture of ethylene carbonate and / or propylene carbonate and an organic solvent having a boiling point of 150° C. or less is preferred from the viewpoint of imparting ion conductivity to the polymer (P). As the organic solvent, one type may be used alone, or two or more types may be used in combination at any ratio.
[0040] As described above, in order to suppress the elution of the polymer (P) into the electrolyte when the device is used, an electrolyte containing the polymer (P) may be used at the time of manufacturing the device. In this case, the amount of the polymer (P) relative to the electrolyte may be in the same range as that described above. Specifically, the amount of the polymer (P) relative to 100 parts by mass of the electrolyte may be preferably 5 parts by mass or more, more preferably 10 parts by mass or more, and even more preferably 15 parts by mass or more. The upper limit of the amount of the polymer (P) relative to 100 parts by mass of the electrolyte is not particularly limited, but may be, for example, 50 parts by mass or less.
[0041] The insulating layer can be disposed between the positive electrode and the negative electrode. By providing an insulating layer, conduction due to contact between the positive electrode and the negative electrode can be avoided. As the insulating layer, a known one used in an electrochemical device can be used. When the electrochemical device is a lithium ion secondary battery, an example of the insulating layer is the separator described in JP 2012-204303 A. Since the insulating layer can be made thin, and the ratio of the electrode active material inside the device can be increased to increase the capacity per volume, a porous film made of a polyolefin resin (polyethylene, polypropylene, polybutene, polyvinyl chloride, etc.) is preferable as the material of the insulating layer. Alternatively, an insulating layer further provided with a porous layer provided on the surface of such a resin porous film using the coating liquid for electrochemical devices of the present invention is also preferable.
[0042] Specific examples of the electrochemical device of the present invention include various non-aqueous primary batteries, secondary batteries, electric double layer capacitors, electric double layer transistors, electrochromic display materials, electrochemical light emitting devices, electrochemical actuators, and dye-sensitized solar cells. Examples of batteries include lithium primary batteries, lithium ion secondary batteries, lithium metal secondary batteries, sodium ion batteries, potassium ion batteries, magnesium ion batteries, aluminum ion batteries, and air batteries. The battery is particularly preferably a lithium ion primary battery or a lithium ion secondary battery.
[0043] The method for producing the electrochemical device of the present invention is not particularly limited, and the device can be produced according to a known method for producing the device using the above-mentioned components. For example, the device can be produced by stacking a positive electrode and a negative electrode with an insulating layer interposed therebetween, rolling or folding the stack according to the battery shape as necessary, placing the stack in a battery container, injecting an electrolyte into the battery container, and sealing the container. In order to prevent the occurrence of an internal pressure rise in the secondary battery, overcharging and discharging, etc., a fuse, an overcurrent prevention element such as a PTC element, an expanded metal, a lead plate, etc. may be provided as necessary. The shape of the device may be, for example, a coin type, a button type, a sheet type, a cylindrical type, a square type, a flat type, or any other type.
[0044] [3. Coating fluid for electrochemical devices] The coating fluid for electrochemical devices of the present invention is a coating fluid that can be used to form layered structures such as electrodes, insulating layers, and undercoat layers that are components of electrochemical devices.
[0045] The coating liquid of the present invention contains a polymer (P). The polymer (P) and preferred examples thereof are the same as those described above as the polymer (P) and preferred examples thereof in the electrochemical device of the present invention. However, the polymer (P) in the electrochemical device may be R P In the case where a crosslinked structure is formed in the coating liquid, the polymer (P) contained in the coating liquid is R P In view of ease of handling during production and ease of obtaining a crosslinked structure in the resulting product, it is particularly preferable to use one containing a crosslinkable partial structure.
[0046] The coating liquid of the present invention may further contain a solvent. Examples of the solvent include water, organic solvents such as N-methylpyrrolidone, and mixtures thereof. The solvent volatilizes during the manufacturing process of the layered structure using the coating liquid and is completely removed or only a trace amount remains.
[0047] The coating liquid of the present invention preferably has a viscosity of a specific high value. The viscosity is preferably 5 cP or more, more preferably 10 cP or more. The upper limit of the viscosity is not particularly limited, but can be, for example, 100,000 cP or less. The ratio of the polymer (P) in the coating liquid of the present invention is 5:95 or more, more preferably 7:93 or more, and even more preferably 9:91 or more, in terms of the ratio of the polymer (P) to the solvent on a mass basis. The upper limit of the ratio of the polymer (P) is not particularly limited, but can be, for example, 50:50 or less. The viscosity is measured using a B-type viscometer at 25°C and 6 rpm. When the viscosity is equal to or greater than the lower limit, a coating with less sharpness or smearing can be obtained.
[0048] The coating liquid of the present invention may have a slurry-like property. Specifically, particles or fibers insoluble in the solvent constituting the coating liquid are suspended throughout almost the entire coating liquid, and the coating liquid has no fixed shape and exhibits fluidity. The preferred viscosity range of the slurry is 10 to 100,000 cP. By having the slurry-like property, it is possible to easily form a layered structure such as an electrode, including processes such as coating on a current collector and drying.
[0049] [4. Coating fluid for electrodes] The coating liquid for an electrode (i.e., a coating liquid that can be used to form an electrode) among the coating liquids for electrochemical devices of the present invention will be described. The coating liquid for an electrode can be a slurry-like coating liquid containing a particulate active material, a polymer (P) and a solvent.
[0050] As the active material constituting the particulate active material, a material known to be contained as an active material in a composite layer of an electrode can be appropriately selected. When the coating liquid is for forming a composite layer of a positive electrode or a negative electrode of a lithium ion secondary battery, examples of the compound constituting the active material for the positive electrode include compounds containing lithium atoms, such as lithium cobalt oxide (LCO), lithium iron phosphate (LFP), and lithium titanate (LTO). Examples of the compound constituting the active material for the negative electrode include graphite, amorphous carbon, silicon, silicon oxide, metallic lithium, and the like.
[0051] From the viewpoint of enabling the electrode to exhibit the desired performance well, the particle size of the particulate active material is preferably 0.1 μm or more, more preferably 0.5 μm or more, and is preferably 50 μm or less, more preferably 40 μm or less. The particle size may be a number average particle size.
[0052] The ratio of the particulate active material and the polymer (P) in the electrode coating liquid can be appropriately adjusted to a range in which the electrode can exhibit the desired performance. Specifically, the ratio of the polymer (P) to 100 parts by mass of the particulate active material is preferably more than 1 part by mass, more preferably 1.5 parts by mass or more, and is preferably 20 parts by mass or less, more preferably 10 parts by mass or less. The viscosity of the coating liquid containing the polymer (P) increases depending on its concentration, so the concentration of the polymer (P) can be appropriately adjusted from the viewpoint of keeping the concentration of the coating liquid in an appropriate range. Compared to conventional viscosity modifiers such as CMC (carboxymethyl cellulose), the increase in viscosity with respect to an increase in the concentration of the polymer (P) is gentle, so that the viscosity can be easily adjusted by adjusting the viscosity using the polymer (P). Furthermore, the polymer (P) has a smaller degree of inhibition of ion migration in the mixture layer than conventional viscosity modifiers such as CMC.
[0053] The electrode coating liquid may contain optional components in addition to the particulate active material, the polymer (P) and the solvent. The optional components may be appropriately selected from components known to be contained in the composite layer as constituent elements of the composite layer.
[0054] Examples of optional components include various polymers other than the polymer (P) that are conventionally known to be used as binders. By appropriately blending such polymers, the mechanical strength of the composite layer can be further improved. Examples of such polymers include PVDF (polyvinylidene fluoride), PVDF-HFP (vinylidene fluoride-hexafluoropropylene copolymer), PTFE (polytetrafluoroethylene), CMC (carboxymethylcellulose), alginic acid, polyacrylic acid, PAN (polyacrylonitrile), SBR (-Lx) (styrene-butadiene rubber latex), NBR (-Lx) (nitrile-butadiene rubber latex), BR (-Lx) (butadiene rubber latex), ACR (-Lx) (acrylic rubber latex), polyethylene oxide, and combinations thereof. When the electrode coating liquid contains the polymer (P) and other binders, the proportion of the polymer (P) in the total is preferably 10% by mass or more, more preferably 20% by mass or more. When the proportion of the polymer (P) is equal to or more than the lower limit, sufficient ion conductivity can be imparted to the binder component.
[0055] Further examples of optional components include particulate components that improve the functionality of the composite layer, such as conductive materials. Known conductive materials such as acetylene black, graphite, graphene, and carbon nanotubes can be used.
[0056] Examples of optional components other than those mentioned above include thickeners, dispersants, leveling agents, antioxidants, defoamers, wetting agents, pH adjusters, and combinations thereof. From the viewpoint of exhibiting the performance of the electrode coating liquid by the particulate active material and the polymer (P), it is preferable that the proportion of optional components is small. Specifically, the total proportion of the particulate active material, conductive material, and polymer (P) to the entire solid content (components other than the solvent, i.e., components that do not volatilize and remain when the composite layer is formed) in the electrode coating liquid is preferably 90% by mass or more, more preferably 95% by mass or more. The upper limit of such a proportion may be 100% by mass.
[0057] The method for preparing the electrode coating fluid is not particularly limited, and the electrode coating fluid can be prepared, for example, by mixing the above-mentioned components.
[0058] 5. Electrodes for electrochemical devices The electrode of the present invention is an electrode that can be a component of the electrochemical device of the present invention. The electrode of the present invention can include a porous composite layer and a current collector. The electrode of the present invention includes a particulate active material and a polymer (P). The particulate active material and the polymer (P) are usually components of the composite layer. The composite layer can further include optional components for constituting the electrode. The particulate active material, the polymer (P), the optional components, preferred examples thereof, and the content ratios thereof in the composite layer are the same as those described above as examples of the electrode coating liquid.
[0059] The ratio of the particulate active material and the polymer (P) in the electrode of the present invention can be the same as that in the electrode coating liquid described above. That is, the ratio of the polymer (P) to 100 parts by mass of the particulate active material in the composite layer is preferably more than 1 part by mass, more preferably 1.5 parts by mass or more, and is preferably 20 parts by mass or less, more preferably 10 parts by mass or less.
[0060] However, in the manufacture of the device, after the electrode is impregnated with the electrolyte, the polymer (P) may gel inside the composite layer over time, and the polymer (P) may dissolve from the composite layer. Due to the occurrence of such dissolution, the ratio of the particulate active material and the polymer (P) in the composite layer may vary over time. The amount and rate of dissolution of the polymer (P) may vary depending on various conditions such as the type of polymer (P), the amount of the polymer (P) contained in the electrolyte, and the storage and use conditions of the device. The proportion of the polymer (P) at the time of manufacture may be higher than the lower limit value described above so that the ratio of the polymer (P) in the composite layer is equal to or higher than the lower limit described above during the entire period of use of the device. In addition, as described above, by adding the polymer (P) to the electrolyte at the time of manufacture of the device, the dissolution of the polymer (P) after manufacture can be suppressed.
[0061] In the composite layer, the polymer (P) may be uniform throughout, or may be unevenly distributed in a portion of the composite layer. For example, the polymer (P) may have a gradient in which the concentration is low inside the composite layer and high on the surface (exposed surface or interface with another layer) of the composite layer. When such a gradient is present, the mechanical strength of the composite layer surface can be efficiently increased, which is particularly preferable. When a polymer such as PVDF or CMC is used alone, the uneven distribution may improve the strength, but since it does not exhibit ion permeability, the uneven distribution may adversely affect the characteristics of the device.
[0062] The thickness of the composite layer in the electrode of the present invention can be appropriately adjusted so as to obtain the desired performance. Specifically, the thickness of the composite layer is preferably 5 μm or more, more preferably 10 μm or more, and is preferably 1000 μm or less, more preferably 600 μm or less.
[0063] The current collector in the electrode of the present invention may be a metal foil. Examples of metals constituting the foil include copper, aluminum, lithium, stainless steel, titanium, molybdenum, iron, and nickel. The thickness of the current collector is preferably 5 μm or more, more preferably 8 μm or more, and is preferably 100 μm or less, more preferably 50 μm or less.
[0064] The electrode of the present invention may include any layer in addition to the composite layer and the current collector. For example, the electrode may include an undercoat layer interposed between the composite layer and the current collector. The undercoat layer will be described later.
[0065] The electrode of the present invention can be manufactured by curing the electrode coating liquid. Specifically, the electrode can be manufactured by applying the electrode coating liquid to the surface of a current collector to form a coating liquid layer, curing the coating liquid layer, and forming a composite layer. The electrode coating liquid can be cured by drying and heating the coating liquid layer to volatilize the solvent, and further applying pressure to the layer as necessary. When a polymer (P) having a crosslinkable group is used, a reaction to form a crosslinked structure is carried out as necessary, thereby obtaining a composite layer containing the polymer (P) having a crosslinked structure.
[0066] When pressure treatment is performed to form the mixture layer, the conditions of the pressure treatment can be adjusted so that the density of the mixture layer obtained is a desired value. The density of the mixture layer is, for example, 0.5 to 6.0 g / cm 3 When the pressure treatment is performed, the particulate shape of the particulate active material is transferred to the current collector, and unevenness can be formed at the interface (i.e., the surface in contact with the composite layer). The height of the unevenness is preferably 500 nm or more, more preferably 800 nm or more. The value of the height of the unevenness is the maximum height Ry specified by JIS. The upper limit of the height of the unevenness is not particularly limited, but can be 3000 nm or less. It is more preferable that the ten-point average roughness Rz is 500 nm or more. By forming such unevenness, particles such as active material are held and the adhesion between the composite layer and the current collector can be improved. The presence of unevenness is preferable from the viewpoint of strengthening the adhesion of the composite layer and suppressing falling off or peeling, and from the viewpoint of suppressing the misalignment between the composite layer and the current collector, but the unevenness may be formed during pressing, or it is also a preferred embodiment to use a current collector foil that has unevenness in advance. To form unevenness on the current collector, for example, mechanical processing such as hitting or rubbing or chemical processing such as etching can be used.
[0067] [6. Insulating layer] The insulating layer of the present invention includes a layer formed by curing the coating liquid for electrochemical devices of the present invention. The insulating layer may be a layer having a multi-layer structure including, for example, a resin layer made of a porous resin generally used as a separator, and a porous layer containing a polymer (P) provided on the surface of the resin layer. The porous layer may contain non-conductive inorganic particles, etc., used as a constituent material of a porous membrane, in addition to the polymer (P). The insulating layer of the present invention has such a structure, and can exhibit good performance as an insulating layer while being well impregnated with an electrolytic solution. The thickness of the porous layer containing the polymer (P) in the insulating layer is preferably 200 μm or less. The lower limit of the thickness is not particularly limited, but may be 1 μm or more. The coating liquid for forming the porous layer may be a liquid containing the polymer (P), particles for forming pores, and a solvent. The liquid is applied to the surface of the resin layer and cured to form a porous layer, thereby obtaining the insulating layer of the present invention.
[0068] [7. Undercoat Layer] In general, an undercoat layer can be present as an intervening layer between two layers that make up an electrochemical device (eg, between a current collector and a composite layer). The undercoat layer of the present invention includes a layer obtained by curing the coating liquid for electrochemical devices of the present invention, and may be composed of only a layer obtained by curing the coating liquid for electrochemical devices of the present invention. That is, the undercoat layer may have a single layer structure including a polymer (P). The undercoat layer may include conductive microstructures such as conductive particles or conductive fibers in addition to the polymer (P). The particle diameter of the conductive particles or the fiber diameter of the conductive fibers may be smaller than the particle diameter of the particulate active material in the composite layer. By providing an undercoat layer between the current collector and the composite layer, it is possible to improve the mechanical adhesion between them and reduce the electrical resistance between them. The coating liquid for forming the undercoat layer may be a liquid including a polymer (P), a conductive microstructure, and a solvent. The undercoat layer can be formed by applying such a liquid to the surface of another layer such as a current collector and curing it. EXAMPLES
[0069] The present invention will be described in detail below with reference to examples. However, the present invention is not limited to the examples shown below, and can be modified and carried out as desired without departing from the scope of the claims of the present invention and the scope of equivalents thereto.
[0070] In the following description, the units "%" and "parts" that represent amounts are by weight unless otherwise specified. Furthermore, the operations described below were carried out under room temperature and normal pressure conditions unless otherwise specified.
[0071] In the following, the following polymers were used. Among these, polymer 1, polymer 2, comparative polymer C1, comparative polymer C2, comparative polymer C3, comparative polymer C4, and comparative polymers C5 to C7 were purchased and used as they were. Polymer 1: Poly-2-ethyl-2-oxazoline (manufactured by Aldrich, 373974, mass average molecular weight 500,000, molecular weight distribution 3 to 4) Polymer 2: Poly-2-ethyl-2-oxazoline (manufactured by Aldrich, 372854, mass average molecular weight 200,000, molecular weight distribution 3 to 4) Polymer 3: Poly-2-ethyl-2-oxazoline (mass average molecular weight 60,000) Polymer 4: Ester polymer of acrylic acid and poly-2-ethyl-2-oxazoline having a terminal hydroxyl group (mass average molecular weight 200,000) Polymer 5: Ester polymer of acrylic acid and poly-2-methyl-2-oxazoline having a terminal hydroxyl group (mass average molecular weight 130,000) Polymer 6: Poly(ethyleneimine-2-ethyloxazoline) copolymer (mass average molecular weight 440,000) Comparative polymer C1: Carboxymethyl cellulose (Daicel Chemical Industries, Ltd., Daicel 1110) Comparative polymer C2: Poly-2-ethyl-2-oxazoline (manufactured by Aldrich, 741906, mass average molecular weight 10,000, molecular weight distribution 1.5 or less) Comparative polymer C3: Poly-2-methyl-2-oxazoline (manufactured by Aldrich, 795283, number average molecular weight 5,000, molecular weight distribution 1.3 or less) Comparative polymer C4: Polyethylene oxide (Aldrich, 181994, viscosity average molecular weight 200,000) Comparative polymer C5: Polyvinylidene fluoride (Solef (registered trademark) 5130 manufactured by SOLVAY, mass average molecular weight 1,000,000) Comparative polymer C6: Poly-2-ethyl-2-oxazoline (manufactured by Aldlich, 372846, mass average molecular weight 50,000, molecular weight distribution 3 to 4) Comparative polymer C7: Poly-2-ethyl-2-oxazoline (manufactured by Aldlich, 741884, mass average molecular weight 35,000, number average molecular weight 25,000, molecular weight distribution 1.4)
[0072] [Production Example 1: Polymer 3] A mixture was prepared by mixing poly-2-ethyl-2-oxazoline having a mass average molecular weight of 50,000 and poly-2-ethyl-2-oxazoline having a mass average molecular weight of 100,000 in a mass ratio of 4:1. This mixture was used as polymer 3 below.
[0073] [Production Example 2: Polymer 4] Poly-2-ethyl-2-oxazoline having a hydroxyl group at the end (comparative polymer C7) was dissolved in dichloromethane and reacted with acryloyl chloride in the presence of triethylamine at 25°C for 48 hours to obtain a macromonomer. This macromonomer was an acrylate in which an acryloyl group was bonded to the end of the 2-ethyl-2-oxazoline chain. This macromonomer was polymerized in acetonitrile using azobisisobutyronitrile as an initiator at 60°C for 120 hours to obtain polymer 4. The mass average molecular weight and molecular weight distribution of polymer 4 were measured by GPC, and the mass average molecular weight was 200,000 and the molecular weight distribution was 2.3.
[0074] [Production Example 3: Polymer 5] Poly-2-methyl-2-oxazoline (comparative polymer C3) having a hydroxyl group at the end was dissolved in dichloromethane and reacted with acryloyl chloride in the presence of triethylamine at 25°C for 48 hours to obtain a macromonomer. This macromonomer was an acrylate in which an acryloyl group was bonded to the end of the 2-methyl-2-oxazoline chain. This macromonomer was polymerized in water at 60°C for 24 hours using V-50 (Fujifilm Wako Pure Chemical Industries) as an initiator to obtain polymer 5. The mass average molecular weight and molecular weight distribution of polymer 4 were measured by GPC, and the mass average molecular weight was 130,000 and the molecular weight distribution was 2.0.
[0075] [Production Example 4: Polymer 6] Partial hydrolysis of polymer 1 was carried out. Specifically, polymer 1 was dissolved in 0.1 M hydrochloric acid and heated and stirred at 120° C. for 5 hours, whereby polymer 6 was obtained in which 12% of the amide structures were hydrolyzed to imine structures. The proportion of hydrolyzed units was 1 Calculated from H-NMR.
[0076] Example 1-1 (1-1-1. Positive electrode) The planetary mixer uses LiFePO as the positive electrode active material. 4 A slurry composition for a lithium ion secondary battery positive electrode was prepared by adding 100 parts of a particulate active material (particulate active material; number average particle diameter 1 μm), 5 parts of acetylene black as a conductive material (HS-100, manufactured by Denki Kagaku Kogyo Co., Ltd.), and 2 parts of a 9% aqueous solution of polymer 1 as a binder in terms of solid content of polymer 1, and further adding and mixing ion-exchanged water as a dispersion medium so that the total solid content concentration was 61%.
[0077] The positive electrode slurry composition was applied to an aluminum foil having a thickness of 20 μm and Rz=0.36 μm as a positive electrode current collector with a coating amount of 8 mg / cm using a comma coater. 2The laminate was dried by conveying it through an oven at 60°C for 2 minutes at a speed of 0.5 m / min, and then heated at 120°C for 2 minutes. This operation resulted in a positive electrode blank having a layer structure of (positive electrode current collector layer) / (positive electrode dried slurry layer).
[0078] The positive electrode raw material was pressed with a roll press. The pressing conditions were such that the density of the resulting positive electrode mixture layer was 2.00 g / cm 3 In order to remove the dispersion medium, the positive electrode raw sheet after the pressure treatment was placed in a vacuum environment at a temperature of 120° C. for 3 hours. By this operation, a positive electrode having a layer structure of (positive electrode current collector layer) / (positive electrode mixture layer) was obtained.
[0079] (1-1-2. Secondary battery) The positive electrode obtained in (1-1-1) was cut into a circle having a diameter of 12 mm to obtain a circular positive electrode. A lithium metal foil (thickness: 200 μm) was cut into a circle having a diameter of 14 mm to obtain a circular negative electrode. A single-layer polypropylene separator was cut into a circle having a diameter of 19 mm to obtain a circular separator. A coin-shaped stainless steel outer container equipped with a polypropylene packing and a 0.2 mm-thick stainless steel cap that fits over the opening of the coin cell CR2032 were prepared.
[0080] A circular positive electrode, a circular separator, and a circular negative electrode were stacked in this order. The circular positive electrode was oriented so that the surface on the positive electrode mixture layer side was in contact with the circular separator. The stack was stored in an outer container. An electrolyte (solvent: EC / EMC = 3 / 7 (mass ratio), electrolyte: LiPF with a concentration of 1M) was placed in the outer container. 6 ) was poured into the container so that no air remained in the container, and a cap was fitted and fixed to the outer container via a packing, and the outer container was sealed to produce a lithium-ion secondary battery with a diameter of 20 mm and a thickness of about 3.2 mm. The amount of electrolyte poured was 160 mg, and the excess electrolyte was wiped off.
[0081] (1-1-3.Discharge amount maintenance rate) The lithium ion secondary battery prepared in (1-1-2) was measured for the discharge amount retention rate under an environment of 25°C. Between 2.50 and 4.00V, constant current charging and discharging of 0.1C was performed, and the discharge capacity C1 at this time was measured. Then, CC charging was performed at a constant current of 0.1C, and after reaching 4.0V, CV charging was performed until the current value became 0.002C, and further discharge at a constant current of 0.1C was performed 10 times, and the discharge capacity C10 of the 10th charge and discharge was measured. From the values of C1 and C10, the discharge amount retention rate ΔC=(C10 / C1)×100(%) was calculated. The larger the discharge amount retention rate ΔC and the closer it is to 100%, the higher the ability to maintain the discharge amount. The obtained discharge amount retention rate ΔC was 99%.
[0082] (1-1-4.Resistance maintenance rate) The resistance retention rate of the lithium ion secondary battery prepared in (1-1-2) was calculated in an environment at a temperature of 25°C. The resistance retention rate ΔR=(V1c-V1d) / (V10c-V10d) was calculated from the charge voltage V1c in the first cycle, the discharge voltage V1d in the first cycle, the charge voltage V10c in the tenth cycle, and the discharge voltage V10d in the tenth cycle in the measurement of the discharge amount retention rate in (1-1-3). The larger the resistance retention rate ΔR and the closer it is to 1, the higher the ability to suppress an increase in resistance. The obtained resistance retention rate ΔR was 1.0.
[0083] (1-1-5. Mechanical stress resistance) The positive electrode obtained in (1-1-1) was cut out to obtain a rectangular sample of 1 cm × 5 cm. The sample was then placed in an electrolyte (1M LiPF 6 The sample was immersed in a 3 / 7 (mass ratio) solvent (EC / EMC) and folded with the positive electrode composite layer facing outward, and the folded area was observed to evaluate the mechanical stress resistance. As a result, no detachment of the positive electrode composite layer was observed.
[0084] (1-1-6. Presence or absence of unevenness) The positive electrode obtained in (1-1-1) was cut with a cross-section polisher to form a cross section parallel to the thickness direction, and observed with a scanning electron microscope. As a result, it was found that the particles of the positive electrode active material and conductive material were embedded in the current collector layer, forming unevenness. When the roughness of the unevenness was measured, the maximum height Ry was 1.1 μm, and the ten-point average roughness Rz was 0.76 μm.
[0085] [Examples 1-2 to 1-4] The coating amount of the positive electrode slurry composition in (1-1-1) is 10 mg / cm 2 (Example 1-2), 12 mg / cm 2 (Examples 1-3), or 14 mg / cm 2 A positive electrode blank was obtained by the same procedure as in (1-1-1) of Example 1-1, except that the positive electrode blank was changed to (Example 1-4). The mechanical stress resistance of the obtained positive electrode blank was evaluated by the same procedure as in (1-1-5) of Example 1-1. As a result, no detachment of the positive electrode composite layer was observed.
[0086] Comparative Example 1-1 A battery was obtained and evaluated in the same manner as in Example 1-1, except for the following changes. In the production of the positive electrode of (1-1-1), the polymer 1 was replaced with the comparative polymer C1. The amount of ion-exchanged water added was changed, and the total solids concentration of the slurry composition for lithium-ion secondary battery positive electrodes was set to 50%.
[0087] The obtained discharge capacity retention rate ΔC was 99%. The obtained resistance retention rate ΔR was 2.0, which means that the resistance of the electrode had doubled after 10 charge / discharge cycles. When mechanical stress resistance was evaluated, it was confirmed that the positive electrode mixture layer fell off from the bent portion, and the aluminum foil of the positive electrode current collector was exposed in a linear shape at the bent portion. When the roughness of the projections and recesses was measured, the maximum height Ry was 1.2 μm and the ten-point average roughness Rz was 0.87 μm.
[0088] [Comparative Examples 1-2 to 1-4] An attempt was made to obtain a positive electrode by the same procedure as in Example 1-1 (1-1-1), except for the following changes. In the production of the positive electrode of (1-1-1), the polymer 1 was replaced with the comparative polymer C1. The amount of ion-exchanged water added was changed, and the total solids concentration of the slurry composition for lithium-ion secondary battery positive electrodes was set to 50%. The coating amount of the positive electrode slurry composition in (1-1-1) is 10 mg / cm 2 (Comparative Example 1-2), 12mg / cm 2 (Comparative Examples 1-3), or 14 mg / cm 2 (Comparative Example 1-4). However, in all of Comparative Examples 1-2 to 1-4, large cracks occurred in the direction along the coating direction of the comma coater, and the positive electrode mixture layer peeled off from the current collector foil, making it impossible to obtain a positive electrode. This is thought to be because the CMC could not withstand the mechanical stress associated with the dimensional changes caused by heating and drying.
[0089] [Examples 1-5 to 1-8] Except for the following changes, the same procedures as in Example 1-1 were followed to obtain and evaluate the battery. In the production of the positive electrode of (1-1-1), instead of using 2 parts of polymer 1, 1 part each of a mixture of 1 part of polymer 1 and 1 part of CMC is used. The amount of ion-exchanged water added was changed to make the total solids concentration of the slurry composition for lithium-ion secondary battery positive electrodes 52%. The coating amount of the positive electrode slurry composition in (1-1-1) is 10 mg / cm 2 (Examples 1-6), 12 mg / cm 2 (Examples 1-7), or 14 mg / cm 2 (Example 1-8) (8 mg / cm in Example 1-5) 2 ). The positive electrode can be produced without cracks (which occurred in Comparative Examples 1-2 to 1-4).
[0090] Example 2 Except for the following changes, the same procedures as in Example 1-1 were followed to obtain and evaluate the battery. In the production of the positive electrode of (1-1), 4 parts of polymer 2 are used in place of polymer 1.
[0091] In this embodiment, the discharge amount retention rate ΔC was 99%, and the resistance retention rate ΔR was 1.0. In addition, in terms of mechanical stress resistance, no detachment of the positive electrode mixture layer was observed, and the performance was equivalent to that of Example 1 in all items.
[0092] Example 3 Except for the following changes, the same procedures as in Example 1-1 were followed to obtain and evaluate the battery. In the production of the positive electrode of (1-1), 3 parts of polymer 4 are used in place of polymer 1.
[0093] In the case of this embodiment, performance equivalent to that of the first embodiment can be expected in terms of both the discharge amount maintenance rate ΔC and the mechanical stress resistance.
[0094] Example 4 Except for the following changes, the same procedures as in Example 1-1 were followed to obtain and evaluate the battery. In the production of the positive electrode of (1-1), 3 parts of polymer 5 are used in place of polymer 1.
[0095] In the case of this embodiment, performance equivalent to that of the first embodiment can be expected in terms of both the discharge amount maintenance rate ΔC and the mechanical stress resistance.
[0096] Comparative Example 2 A battery was produced in the same manner as in Example 1, except that in the production of the positive electrode (1-1), Comparative Polymer C2 was used instead of Polymer 1. In this case, when the positive electrode raw material was pressed by a roll press machine, the layer of the dried positive electrode slurry peeled off from the current collector layer, and cracks occurred in the layer of the dried positive electrode slurry, so that a positive electrode could not be obtained.
[0097] Example 5-1 The planetary mixer uses LiCoO as a positive electrode active material. 2A slurry composition for a lithium ion secondary battery positive electrode was prepared by adding 100 parts of Cellseed C (manufactured by Nippon Chemical Industry Co., Ltd., particulate active material; number average particle size 20 μm), 2.1 parts of acetylene black as a conductive material (manufactured by Denki Kagaku Kogyo Co., Ltd., HS-100), and 1.6 parts of an 8% NMP solution of Polymer 1 as a binder in terms of solid content of Polymer 1, and further adding and mixing NMP as a dispersion medium so that the total solid content concentration was 81%. The positive electrode slurry composition was applied to a 20 μm-thick aluminum foil as a positive electrode current collector with a comma coater in a coating amount of 20 mg / cm. 2 A multi-layered product having a layer structure of (positive electrode current collector layer) / (positive electrode slurry composition layer) was obtained. A long aluminum foil having a width of 12 cm was used, and coating was performed in an 8 cm wide region in the center of the width direction by moving a comma coater in a direction parallel to the longitudinal direction. The laminate was dried by conveying it through an oven at 60° C. for 2 minutes at a speed of 0.5 m / min, and then heat-treated for 2 minutes at 120° C. By this operation, a positive electrode blank having a layer structure of (positive electrode current collector layer) / (positive electrode dried slurry layer) was obtained. The positive electrode raw material was pressed with a roll press. The pressing conditions were such that the density of the resulting positive electrode mixture layer was 3.90 g / cm 3 In order to remove the dispersion medium, the positive electrode raw sheet after the pressure treatment was placed in a vacuum environment at a temperature of 120° C. for 3 hours. By this operation, a positive electrode having a layer structure of (positive electrode current collector layer) / (positive electrode mixture layer) was obtained.
[0098] The amount of warping of the obtained positive electrode was measured. The amount of warping was measured by placing the positive electrode on a horizontal stand with the surface of the positive electrode composite layer facing up, and measuring the distance between the surface of the stand and the center of the width direction of the lower surface of the positive electrode composite layer. The amount of warping was 0.1 cm.
[0099] Comparative Example 3 A positive electrode was obtained by the same procedure as in Example 5-1, except that an 8% NMP solution of Comparative Polymer C5 was used as the binder instead of the 8% NMP solution of Polymer 1 (the amount added was 1.6 parts as the solid content of Comparative Polymer C5, the same as in Example 5-1), and the amount of warping was measured. The obtained positive electrode was significantly warped, drawing an arch in the width direction. This is considered to indicate that the residual amount of stress due to the processing history was large. If the warping is large, it is difficult to fabricate an electrochemical device, and this is not preferable. The amount of warping was 1.8 cm.
[0100] Example 5-2 A positive electrode was obtained by the same procedure as in Example 5-1 except for the following changes, and the amount of warping was measured. Instead of using an 8% NMP solution of polymer 1 as a binder, a combination of an 8% NMP solution of polymer 1 and an 8% NMP solution of comparative polymer C5 was used. The amounts of these used were 0.8 parts as the solid content of polymer 1 and 0.8 parts as the solid content of comparative polymer C5, respectively. The amount of warping was 0.8 cm.
[0101] [Reference Example 1: Measurement of potential window] To confirm the electrochemical stability of the polyoxazolines, linear sweep voltammetry (LSV) was performed. Polymer 1 in 1M LiPF 6 The polymer was dissolved in a solvent (solvent; EC / EMC=3 / 7, mass ratio) at a concentration of 10% to prepare a polymer solution. The working electrode, counter electrode, and reference electrode were immersed in the polymer solution, and the first potential sweep was performed. The working electrode was a conductive carbon-coated electrode with a surface area of 2 cm. 2 Aluminum foil (dimensions 1 cm x 1 cm) was used. Lithium metal foil was used as the counter electrode and reference electrode. The sweep was performed from the natural potential to Li / Li + The test was performed at 1 mV / s over a range up to 4.8 V. Next, the working electrode is attached to a copper foil (surface area 2 cm 2 , dimensions 1cm × 1cm) and the natural potential was changed to Li / Li + A second potential sweep was performed at 1 mV / s to −0.5 V vs. The results are shown in Figure 1. In Figure 1, the dashed line shows the results of the first potential sweep, and the solid line shows the results of the second potential sweep. From the results in Figure 1, polyoxazoline has a maximum potential of at least 0 to 4.8 V (vs Li / Li + ), making it suitable as a material for electrochemical devices.
[0102] Example 6: Thermal stress resistance Polymer 1 in 1M LiPF 6 The polymer was dissolved in an electrolyte (solvent: propylene carbonate) at a concentration of 6% by mass to prepare a polymer solution. Initial viscosity of polymer solution η 0 was measured at 25°C using a B-type viscometer. After that, the polymer solution was placed in a thermostatic bath at 60°C for 100 hours, and the viscosity η 1 was measured. 0 and η 1 From the above, the viscosity retention rate ((η 1 / η 0 ) × 100(%) was calculated. The viscosity retention rate was 100%.
[0103] Comparative Example 4 The viscosity retention rate of the polymer solution was determined by the same procedure as in Reference Example 2, except that Comparative Polymer C4 was used instead of Polymer 1. The viscosity retention rate was 30%, which shows that Comparative Polymer C4 is inferior in heat resistance in the electrolyte compared to Polymer 1.
[0104] [Example 7: Alkaline stress resistance] NCA (LiNi 0.82 Co 0.15 Al 0.03 O 2), acetylene black (AB) as a conductive additive, and polymer 2 were weighed in a mass ratio of positive electrode active material:AB:polymer 2=100:2:1.2, and an appropriate amount of N-methylpyrrolidone was added to the mixture, which was then stirred in a planetary mixer to prepare a slurry for the positive electrode of a lithium ion secondary battery. When the liquid properties were checked at 25°C immediately after preparation, it was confirmed that the slurry was flowing. After that, the slurry for the positive electrode was left in an environment of 25°C for 24 hours, and the liquid properties were checked again, and it was confirmed that the slurry was flowing.
[0105] Comparative Example 5 The liquid properties of the positive electrode slurry were confirmed by the same procedure as in Example 7, except that Comparative Polymer C5 was used instead of Polymer 2. When the liquid properties were confirmed at 25°C immediately after preparation, it was confirmed that the slurry was flowing, but when it was confirmed after storage, it was in a gel state and did not flow. The loss of such liquid properties is believed to be due to the high pH of NCA causing a defluorination reaction from PVDF, resulting in gelation.
[0106] [Reference Example 2: Adhesion to substrate] Polymer 3, Comparative Polymer C2, and Comparative Polymer C4 were each dissolved in ion-exchanged water to a concentration of 5 mass% to obtain three types of polymer solutions. Each polymer solution was applied to an aluminum foil, a copper foil, and a stainless steel (SUS304) foil, respectively, and dried to obtain nine types of coating films with a thickness of 50 microns. An attempt was made to peel off the coating film from the foil by picking with tweezers.
[0107] The coating film of Polymer 3 formed on all the foils did not peel off. For the coating film of the comparative polymer C2, of all the coating films formed on the foils, only the portions that were picked off with tweezers fell off. As for the coating film of the comparative polymer C4, the coating film fell off in the form of a film when applied to all the foils.
[0108] [Reference Example 3: Use in combination with non-ion conductive polymer] Polymer 1 and comparative polymer C5 were dissolved in N-methyl-2-pyrrolidone in various ratios to obtain five types of polymer solutions 1 to 5. In each of polymer solutions 1 to 5, the total concentration of polymer 1 and comparative polymer C5 was 8 mass%. In each of polymer solutions 1 to 5, the mass ratio of polymer 1 to comparative polymer C5 was 0:100 (polymer solution 1), 10:90 (polymer solution 2), 20:80 (polymer solution 3), and 50:50 (polymer solution 4).
[0109] Each of the polymer solutions was cast onto a polytetrafluoroethylene tray and dried at 160° C. to remove N-methyl-2-pyrrolidone, obtaining a film having a thickness of 100 μm. 6 The film was immersed in a solvent (solvent; EC / EMC=3 / 7, mass ratio) for 1 hour to allow the electrolyte to penetrate the film. After that, the film was pulled up, the excess electrolyte was wiped off, and the film was sandwiched between two SUS plates, and the ion conduction resistance was measured by the AC impedance method. The results were below the lower limit of measurement (polymer solution 1), 22Ω (polymer solution 2), 10Ω (polymer solution 3), 6Ω (polymer solution 4) and (polymer solution 5). When the film does not contain polyoxazoline polymer, it does not exhibit ion conductivity, but when the proportion of polyoxazoline polymer in the entire film is 10 mass% or more, ion conductivity is observed. This shows that an ion conduction path can be formed by adding polyoxazoline polymer to a polymer that does not have ion conductivity.
[0110] [Reference Example 4: Measurement of solution viscosity] Polymers 1 to 3 and Comparative Polymer C2 were dissolved in ion-exchanged water at room temperature to obtain 5% aqueous solutions. The viscosities of these solutions were measured at 6 rpm and 25° C. using a Brookfield viscometer to find that they were 17, 6.6, 2.6, and 1.3 cP, respectively.
[0111] Each of the polymer solutions was cast onto a polytetrafluoroethylene tray and dried at 160° C. to remove N-methyl-2-pyrrolidone, obtaining a film having a thickness of 100 μm. 6The film was immersed in (solvent; EC / EMC = 3 / 7, mass ratio) for 1 hour to allow the electrolyte to penetrate the film. After that, the film was pulled up, the excess electrolyte was wiped off, and the film was sandwiched between two SUS plates, and the ion conduction resistance was measured by the AC impedance method. The results were below the lower limit of measurement (polymer solution 1), 22Ω (polymer solution 2), 10Ω (polymer solution 3), 6Ω (polymer solution 4) and (polymer solution 5). When the film does not contain polyoxazoline polymer, the film does not exhibit ionic conductivity, but when the proportion of polyoxazoline polymer in the entire film is 10 mass % or more, ionic conductivity is observed. This shows that by adding polyoxazoline polymer to a polymer that does not have ion conductivity, an ionic conduction path can be formed.
[0112] [Example 8: Preparation of coating solution for insulating layer and production of insulating layer] 100 parts of alumina particles with a volume average particle size of 0.6 μm, 1 part of a 1% by mass aqueous solution of polymer 1 in terms of solid content equivalent, and 2 parts of a 1% by mass aqueous solution of comparative polymer C1 in terms of solid content equivalent were added and dispersed using a bead mill, and then ion-exchanged water was mixed so that the solid content concentration was 25% to prepare a slurry for a porous membrane. This slurry was applied onto a polyolefin separator (manufactured by Polypore, Celgard 2325) and dried to obtain a composite separator having an alumina layer with a thickness of 2 μm. This composite separator and the positive electrode obtained in Example 5-1 were laminated together to obtain a thickness of 1 g / cm 2 When the separator and the positive electrode were rubbed together under a load of 1000 MPa, no alumina was observed to fall off from the separator or to be transferred to the positive electrode, and a composite separator with little powder falling off was obtained.
[0113] Comparative Example 6 A composite separator was obtained in the same manner as in Example 8, except that the aqueous solution of Polymer 1 was not blended and only Comparative Polymer C1 was used. This composite separator was laminated with the positive electrode obtained in Comparative Example 3 to obtain a thickness of 1 g / cm 2When the separator was rubbed under a load of 10 ...
[0114] [Example 9: Preparation and application of undercoat liquid] 30 g of polymer 6 was added to 1000 g of ion-exchanged water, and the mixture was stirred at 25°C for 2 hours to completely dissolve the polymer. This solution was introduced into a bead mill equipped with a cooling jacket, and zirconia balls with a diameter of 0.5 mm were added at a filling rate of 80%, and 25 g of acetylene black (HS-100, manufactured by Denki Kagaku Kogyo Co., Ltd.) was added as conductive particles. Dispersion was performed while taking care not to allow the product temperature to exceed 40°C, to obtain a conductive undercoat solution. The undercoat solution was applied to an aluminum foil having a thickness of 20 μm and a surface etched (Rz=4.6 μm) as a current collector using a microgravure coater (MuCoater, manufactured by Yasui Seiki Co., Ltd.), and dried to obtain an undercoat layer having a thickness of 1 μm after drying. The obtained undercoat layer was picked up using tweezers, and an attempt was made to peel the undercoat layer from the foil, and it was confirmed that the undercoat layer was well adhered without peeling.
[0115] Example 10 Two parts of polymer 1, electrolyte (solvent: EC / PC = 5 / 5 (mass ratio)), electrolyte: LiPF with a concentration of 1M 6 ) as a positive electrode active material, and LiCoO 2 100 parts of Nihon Kagaku Kogyo Co., Ltd., Cellseed C, particulate active material; number average particle size 20 μm) and 4 parts of acetylene black as a conductive material (Denki Kagaku Kogyo Co., Ltd., HS-100) were weighed into a mortar and thoroughly kneaded to obtain a clay-like kneaded material. This was spread and attached onto etched aluminum foil (Rz = 6 μm) to produce a lithium ion secondary battery positive electrode with a basis weight of 21 mg.
[0116] Next, 2 parts of polymer 1 were mixed with an electrolyte (solvent: EC / PC = 5 / 5 (mass ratio)) and electrolyte: LiPF 68 parts of the graphite (MCMB, manufactured by MTI Corporation; number average particle size 18 μm) as the negative electrode active material were weighed into a mortar and thoroughly kneaded to obtain a clay-like kneaded product. This was spread and attached onto an etched copper foil (Rz = 5 μm) to produce a lithium ion secondary battery negative electrode with a basis weight of 11 mg.
[0117] The positive electrode was cut to 10cm x 10cm, and the negative electrode to 10.2cm x 10.2cm, and a single-layer polypropylene separator cut to 10.4cm x 10.4cm and soaked in an electrolyte solution (solvent: EC / PC = 5 / 5 (mass ratio)) in which polymer 1 was dissolved at a concentration of 20% was sandwiched between them to form a lithium-ion battery. This laminate exhibited adhesiveness even without any special fixing because the electrolyte solution contained polyoxazoline, and this allowed the laminate to maintain a tightly adhered state. The battery was then placed in an aluminum laminate outer container, and the opening was heat sealed to produce a lithium ion secondary battery. In this process, no additional electrolyte was injected. This lithium-ion secondary battery was able to stably charge and discharge at a charge / discharge rate of 1.0 C in a temperature environment of 25° C., between 3.0 and 4.20 V.
[0118] Example 11 A 10% aqueous solution of polymer 1 was prepared. It was sprayed onto a polypropylene separator cut into a 5 cm square. The amount of the polymer attached to the separator was 0.1 mg / cm. 2 The sprayed separator was sticky in a wet state. When the separator was attached to a 4.8 cm square cut positive electrode produced in Example 5-1, it was integrated and did not easily shift. On the other hand, in the case of a separator not coated with a polymer, the electrode and the separator are not integrated, so that there may be a problem of shifting during the manufacture of the battery. Since polyoxazoline has ion permeability, it does not block the movement of ions even when it is coated on the separator, but when the same operation is performed using, for example, the comparative polymer C1, the pores of the separator are blocked with a membrane that does not allow ions to pass through, which may reduce the output of the battery.
[0119] [Reference example 5] Each of Polymer 1, Polymer 2, Comparative Polymer C6, and Comparative Polymer C7 was dissolved in propylene carbonate to obtain a solution with a concentration of 5% by weight. The viscosity of this solution was measured at 25°C. Next, Li salt (LiTFSI; lithium bistrifluorosulfonylimide) was dissolved in each solution to prepare an electrolyte-like solution. The amount of Li salt added was 0.5 mol / kg relative to the mass of propylene carbonate. The viscosity of the electrolyte-like solution was measured at 25°C, and the viscosity increase rate before and after the addition of the Li salt was calculated. The results are shown in Table 1. All of the polymer solutions showed a fairly low viscosity for their concentrations. Subsequent addition of Li salts resulted in an increase in viscosity in all of the solutions, but a large increase in viscosity due to the addition of Li salts was observed when the mass-average molecular weight was over 50,000. This suggests that the interaction between polymer molecules is particularly strong in the range of mass-average molecular weights exceeding 50,000, which is thought to lead to increased stress resistance of electrochemical devices and their electrodes.
[0120] [Table 1]
Claims
1. A non-aqueous electrochemical device, comprising: The electrochemical device includes an electrode mixture layer and an electrolyte solution enclosed therein, The electrode mixture layer, the electrolyte solution, or both of them contain a polymer (P), The polymer (P) is a polymer having a molecular structure containing a unit (P) represented by the following formula (P) and having a mass average molecular weight of more than 50,000: The amount of the polymer (P) relative to 100 parts by mass of the electrolytic solution is 5 parts by mass or more and 50 parts by mass or less, The electrochemical device, wherein the polymer (P) contains, as the unit (P), a unit in which the R P is a methyl group or an ethyl group. 【Chemistry 1】
2. 2. The electrochemical device according to claim 1, wherein the proportion of said units (P) in said polymer (P) molecules is 50 mass % or more.
3. Further comprising an electrolyte; 3. The electrochemical device according to claim 1, wherein the amount of the polymer (P) is 5 parts by mass or more based on 100 parts by mass of the electrolyte solution.
4. An electrode for a non-aqueous electrochemical device comprising an electrode mixture layer containing a particulate active material and a polymer (P), The polymer (P) is a polymer having a molecular structure containing a unit (P) represented by the following formula (P) and having a mass average molecular weight of more than 50,000: In the electrode mixture layer, the amount of the polymer (P) per 100 parts by mass of the particulate active material is more than 1 part by mass and not more than 20 parts by mass, The electrode for electrochemical devices, wherein the polymer (P) contains, as the unit (P), a unit in which the R P is a methyl group or an ethyl group. 【Chemistry 2】
5. 5. The electrode for electrochemical devices according to claim 4, wherein a ratio of said units (P) in said polymer (P) molecules is 50 mass % or more.
6. The electrode for electrochemical devices according to claim 4 , comprising: a mixture layer containing the particulate active material and the polymer (P); and a current collector layer.
7. 7. The electrode for an electrochemical device according to claim 6, wherein the current collector layer is a metal layer.
8. 8. The electrode for electrochemical devices according to claim 6, wherein the current collector layer has an unevenness of Ry 500 nm or more on a surface thereof in contact with the mixture layer.
9. A coating liquid for an electrochemical device comprising a particulate active material and a polymer (P), The polymer (P) is a polymer having a molecular structure containing a unit (P) represented by the following formula (P) and having a mass average molecular weight of more than 50,000: In the coating liquid, the amount of the polymer (P) per 100 parts by mass of the particulate active material is more than 1 part by mass and not more than 20 parts by mass, The coating fluid for an electrochemical device, wherein the polymer (P) contains, as the unit (P), a unit in which the R P is a methyl group or an ethyl group. 【Chemistry 3】
10. The coating fluid for electrochemical devices according to claim 9 , wherein a ratio of the units (P) in the molecules of the polymer (P) is 50 mass % or more.
11. The coating fluid for electrochemical devices according to claim 9 or 10, which has properties of a slurry.
12. An insulating layer for an electrochemical device, comprising a layer obtained by curing the coating liquid according to any one of claims 9 to 11.
13. The insulating layer according to claim 12 , comprising a crosslinked product of the polymer (P) formed by the curing.
14. An electrode for electrochemical devices, comprising a layer formed by curing the coating liquid according to any one of claims 9 to 11.
15. The electrode according to claim 14 , comprising a crosslinked product of the polymer (P) formed by the curing.
16. An undercoat layer for an electrochemical device, comprising a layer obtained by curing the coating liquid according to any one of claims 9 to 11.
17. The undercoat layer according to claim 16, comprising a crosslinked product of the polymer (P) formed by the curing.
18. An electrolyte solution for electrochemical devices comprising a polymer (P), The polymer (P) is a polymer having a molecular structure containing a unit (P) represented by the following formula (P) and having a mass average molecular weight of more than 50,000: The amount of the polymer (P) relative to 100 parts by mass of the electrolytic solution is 5 parts by mass or more and 50 parts by mass or less, The electrolyte solution for electrochemical device, wherein the polymer (P) contains, as the unit (P), a unit in which the R P is a methyl group or an ethyl group. 【Chemistry 4】
19. The electrolyte solution for electrochemical devices according to claim 18 , wherein a ratio of the units (P) in the molecules of the polymer (P) is 50 mass % or more.
Citation Information
Patent Citations
Nonaqueous secondary battery
JP2003272634A
Nonaqueous electrolyte battery
JP2003346899A
Non-aqueous electrolyte for secondary battery and non-aqueous electrolyte secondary battery
JP2004296104A
Nonaqueous electrolytic solution for secondary battery, and nonaqueous electrolyte secondary battery
JP2004296116A
Method for producing lithium-containing compound oxide and non-aqueous secondary battery
JP2010126422A